Functional Pituitary Networks in Vertebrates - Santiago-Andres, Yorgui; Golan, Matan; Fiordelisio, Tatiana (Frontiers in Endocrinology, 2021)
The pituitary is a master endocrine gland that developed early in vertebrate evolution and therefore exists in all modern vertebrate classes. The last decade has transformed our view of this key organ. Traditionally the pituitary has been viewed as a randomly organized collection of cells that respond to hypothalamic stimuli by secreting their content. However recent studies have established that pituitary cells are organized in tightly wired large-scale networks that communicate with each other in both homo and heterotypic manners, allowing the gland to quickly adapt to changing physiological demands. These networks functionally decode and integrate the hypothalamic and systemic stimuli and serve to optimise the pituitary output into the generation of physiologically meaningful hormone pulses. The development of 3D imaging methods and transgenics models have allowed us to expand the research of functional pituitary networks into several vertebrate classes. Here we review the establishment of pituitary cell networks throughout vertebrate evolution and highlight the main perspectives and future directions needed to decipher the way by which pituitary networks serve to generate hormone pulses in vertebrates.